Semiotic Analysis of Richard Ross’ Art Photography Juvenile-in-Justice - Bolkiah, Faiz; Rahmadi (Universitas Pasundan, 2023)
In art photography, there is an idea that artists want to convey to the public. Because photography records reality, to convey a specific idea it is often necessary to use symbols from real objects that are appropriate so that the viewer can direct his mind to where the artist wants. It is hoped that this research will explain why Richard Ross' work has succeeded in bringing the public in the direction that the artist wants by using the right visual symbols. Then from the method that has been read, novice photography artists can follow the method they use so that the work can become more visually precise.